An Analysis of Students’ Perception Regarding to the Use of Role Play Technique in Learning Speaking Skills - Michael Wijaya; Ika Handayani; Yusti Fargianti (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2024)
This study aimed to find out how are the perception of students regarding to the use of role play technique in learning speaking skills and also what are strengths and weaknesses of it according to students’ perception at SMP Negeri 1 Kelapa Dua, Tangerang. The objectives of the research were to comprehend about how are the perception of students regarding to the use of role play technique in learning speaking skills and also to find out about what are strengths and weaknesses of using role play technique in learning speaking skills according to students’ perception. The research employed a case study method. The data were collected by observation, questionnaire, and interview. The results of the research showed that it helped them in English Vocabulary, English Grammar, English Comprehension, English Pronunciation, and also their English fluency. Moreover, it was more fun and helped them to cultivate their knowledge, made them interested and more enthusiastic, more optimistic, more motivated, taught them about teamwork, involved them directly, and more active. However, it still made them shy and afraid when playing roles. It is also proven to be efficient as a technique in learning speaking skills, but less effective in fostering their self-confidence.